2018
DOI: 10.3390/app8071127
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of Various ZnO/SiO2-Stacked Layers for Flexible Micro-Energy Harvesting Devices

Abstract: Abstract:In this paper, we present a study of various ZnO/SiO 2 -stacked thin film structures for flexible micro-energy harvesting devices. Two groups of micro-energy harvesting devices, SiO 2 /ZnO/SiO 2 micro-energy generators (SZS-MGs) and ZnO/SiO 2 /ZnO micro-energy generators (ZSZ-MGs), were fabricated by stacking both SiO 2 and ZnO thin films, and the resulting devices were characterized. With a particular interest in the fabrication of flexible devices, all the ZnO and SiO 2 thin films were deposited on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…In particular, the sample B of the Ag/ZnO/AlN/Cr/ITO/Al-foil structure showed the highest output voltage. Similarly to other reports [12][13][14], we fabricated additional devices including each material (AlN, SiO 2 , or a-Si) used in our earlier researches for a further study, as shown in Figure 10. Here, each target of AlN (5N, iTASCO), n-type a-Si (5N, iTASCO), or SiO 2 (4N, iTASCO) were used to fabricate the devices shown in Figure 10.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the sample B of the Ag/ZnO/AlN/Cr/ITO/Al-foil structure showed the highest output voltage. Similarly to other reports [12][13][14], we fabricated additional devices including each material (AlN, SiO 2 , or a-Si) used in our earlier researches for a further study, as shown in Figure 10. Here, each target of AlN (5N, iTASCO), n-type a-Si (5N, iTASCO), or SiO 2 (4N, iTASCO) were used to fabricate the devices shown in Figure 10.…”
Section: Resultsmentioning
confidence: 99%
“…For the ZnO deposition in particular, a mixture of 18 sccm Ar and 12 sccm N 2 O gas was flowing during the sputtering process to reduce the free-carrier concentration in the ZnO film, leading directly to the improvement of device performance [16]. Many previously reported devices fabricated on flexible plastic substrates [10,[12][13][14]16,17] have an intrinsic limitation to increasing process temperatures. Thus, in this work, instead of flexible plastic substrates, we have attempted to employ the Al-foil as a substrate to further increase the process temperatures, which helpfully allows for annealing heat treatments at higher temperatures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it has been reported that ZnO and SiO 2 nanoparticles provides a lay down of a novel green nanotechnology to control insect pest including mosquitoes' larvae [5][6][7][8]. ZnO/SiO 2 nanocomposites have been synthesized using various techniques such as chemical vapor deposition, sputtering, chemical etching and sol gel process and they are used in different applications such as an-timicrobial, photonic crystals, photocatalysts, gas sensors, vacuum fluorescent display and varistors etc., [9][10][11][12][13][14][15][16][17][18][19]. But based on our search, there was no report on the effect of ZnO/SiO 2 nanocomposites against mosquito larvae except for the individual ZnO and SiO 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%